Phosphorus Limitation Improved Salt Tolerance in Maize Through Tissue Mass Density Increase, Osmolytes Accumulation, and Na+ Uptake Inhibition - Tang, Hongliang; Niu, Le; Wei, Jing; Chen, Xinying; Chen, Yinglong (Frontiers in Plant Science, 2019)
Low phosphorus (P) availability and salt stress are two major constraints for maize (Zea mays L.) growth in north China. A combination of salinity and high P rather than low P is more detrimental to the growth of maize. However, little is known about the mechanisms by which P nutrition modifies the salt tolerance and P uptake of maize. The present study aimed to investigate the combined effects of salinity and P on maize growth and P uptake, and to address the physiological mechanisms of salt tolerance influenced by P availability in maize. Seedlings of a local maize cultivar XY335 were grown hydroponically for 35 days under low (5 μM) or sufficient P supply (200 μM) with or without 100 mM NaCl. Root morphological traits, tissue mass density, leaf osmolytes (sugars and proline) accumulation, and Na+/K+ ratio were measured to allow evaluation of the combined effects of salinity and P on maize growth and P uptake. Both P deficiency and salinity markedly reduced the growth of maize. However, P deficiency had a more pronounced effect on shoot growth while salinity affected root growth more prominently. Combined effects of P deficiency and salinity on total root length, root surface area, and average root diameter were similar to that of plants grown under salt stress. The combination of P deficiency and salinity treatments had a more pronounced effect on tissue mass density, leaf proline and soluble sugars compared to individual treatment of either low P or NaCl. When exposed to salt stress, maize plants of sufficient P accumulated greater amount of Na+ than those under P deficit, but similar amounts of K+ were observed between the two P treatments. Salt stress significantly increased shoot P concentration of maize with sufficient P (P < 0.01), but not for P-deficient plants. In sum, shoots and roots of maize exhibited different responses to P deficiency and salinity, with more marked effect of P deficiency on shoots and of salinity on roots. P deficiency improved salt tolerance of maize plants, which was associated with the increase of tissue mass density, accumulation of osmolytes, reduction of Na+ accumulation, and selective absorption of K+ over Na+.